Quando em dois somos muitos: histórias de vida dialogadas e a atuação do professor de música na educação básica - Almeida, Jéssica de (2016)
This dissertation is the result of a masters research that aimed to understand how the musical formation of a music teacher focuses on teaching practices in basic education. This research was designed from two specific objectives: a) Identify formative experiences with music and teaching in the life stories of music teachers research participants (graduates of the Music course - Full Degree UFSM); and b) promote dialogue between formation and practice of music teachers in basic education. Data were stated on the oral narratives of life stories of teachers (ABRAHÃO, 2004; JOSSO, 2008; NÓVOA, 1992; OLIVEIRA, 2001, 20016; PERES, 2012; SOUZA, 2006) transiting between musical memories, and between the participants ' relationship with the music and with the teaching of music. Starting from an autobiographical approach, were punctuated the knowledge resulting from the experiences of students and music instruments promoting dialogues between these memories and the formations and acting teachers. With this integration of participants in understanding their own formations, the development of research was characterized as research-training (JOSSO, 2010), triggering processes of teacher's awareness about the formative experiences that they experienced. In the dialogues between participants, were revealed in the formation and knowledge identified periodizations and crucial moments (JOSSO 2004; 2010) in: pedagogical heritage themes (OLIVEIRA; PERES, 2011; ARROYO, 2012, reflections of teachers in their practices (ARROYO, 2013); lesson from the student and experiences with the music education (SOUZA, 2008; SUBTIL, 2007 and 2005; LOURO, 2008; DEWEY, 2011; PEREIRA, 2014) discussing the children's relationships with music (RAMOS, 2002; PONSO, 2011; PEDRINI 2013; WERLE, 2015); discussions about the University and relations with practice (MATEIRO, 2009 and 2003; PENNA, 2010). Horizontal/comparative analysis (BOLÍVAR; DOMINGO; FERNÁNDEZ, 2001) resulted in two transversal dialogues: 1. The time in independent learning (NÓVOA, 2009; JOSSO, 2010; 2006 and 2004); 2. Profile of professor of music: a project under construction (JOSSO, 2004 and 2007). I hope, with this research, expand the design on the formation of music teacher in basic education, including life experiences related to teaching and music to their teachings.